Death and the maiden : a Max Liebermann mystery - Tallis, Frank (Random House Trade Paperbacks, 2012)
"Ida Rosenkranz is top diva at the Vienna Opera, but she's gone silent for good after an apparent laudanum overdose. Learning of her professional rivalries and her scandalous affairs with older men, Detective Inspector Oskar Rheinhardt and Dr. Max Liebermann suspect foul play instead. Their investigation leads them into dark and dangerous conflicts with Gustav Mahler, the opera's imperious director, who is himself the target of a poison pen campaign, and Karl Lueger, Vienna's powerful and anti-Semitic mayor. As the peril escalates, Rheinhardt grows further into his role as family man, while Liebermann finds himself at odds with his inamorata, Amelia, who's loosening both her corset and her tongue in the new feminist movement."--